2018
DOI: 10.1021/acs.jpcc.7b10511
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Oil Adsorption and Cyclodextrin Extraction Process on Rough Silica Surface by Molecular Dynamics Simulation

Abstract: Molecular dynamics simulation was performed to investigate the adsorption and aqueous extraction of oil contaminants on silica surface with various roughness. The oil dispersion and immersion were characterized by molecular configuration, adsorption energy, and contact angle, while the oil detachment in water and cyclodextrin solution was evaluated by the overall extractability, extractability from the individual groove, and free energy analysis. Results demonstrated that the main resistance for oil release fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 47 publications
1
18
1
Order By: Relevance
“…However, the oil-wetting mode transition was not observed in our previous study where only saturates were present on the rough silica surface. 13 The above findings suggested that it was the asphaltenes that led to the wettability alternation on the rough surface. To confirm this, we removed the asphaltene molecules during the model construction and ran the simulation following the same procedures.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…However, the oil-wetting mode transition was not observed in our previous study where only saturates were present on the rough silica surface. 13 The above findings suggested that it was the asphaltenes that led to the wettability alternation on the rough surface. To confirm this, we removed the asphaltene molecules during the model construction and ran the simulation following the same procedures.…”
Section: Resultsmentioning
confidence: 91%
“…To quantify the penetration capability of each oil fraction on the silica surface, the amount of oil molecules entering the grooves was characterized by counting the number of oil molecules with half of the atoms inside silica grooves. 13 The interaction energies were calculated using the standard modules of Gromacs. The self-diffusion coefficient was computed using the Einstein equation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations